Influence of calcium on white efflorescence formation on dry fermented sausages with co-extruded alginate casings. (May 2020) - Hilbig, Jonas; Hartlieb, Katrin; Herrmann, Kurt; Weiss, Jochen; Gibis, Monika
Graphical abstract: Highlights: Different types of efflorescence are formed at low or high calcium concentrations. Accelerated white efflorescence formation at high calcium concentrations. At high calcium concentrations the crystals are composed of calcium lactate. At low calcium concentrations the crystals are mainly made of magnesium lactate. White efflorescence formation is possible without magnesium. Abstract: The effect of the concentration of calcium in the crosslinking solution during co-extrusion of dry fermented sausages with calcium alginate casing on the white efflorescence was investigated. With the co-extrusion technology, a continuous sausage production is possible and, furthermore, snack products with very small calibers can be produced. Therefore, crosslinking solutions with different concentrations of CaCl2 (15, 20, 25, and 30%) were used during the production. High concentrations of calcium led to a very rapid and intensive white efflorescence formation; the efflorescences covered 90% of the surface of the samples produced with 20–30% of CaCl2 after 8 weeks of storage. However, the batch produced with the lowest amount of CaCl2 showed a slow efflorescence formation and a significantly decreased area covered by it ( 70% after 8 weeks). The differences in the formation were attributed to the excess of calcium on the surface of the sausages (saturated calcium alginate film), therefore leading to rapid complexation of lactate to mostly calcium lactate. Whereas with 15% of CaCl2 in the solution, only small amounts of calcium are not bound by the alginate film, and the formation of white efflorescence is due to the time-delayed formation with magnesium, which diffuses from the core to the surface.